2015
DOI: 10.1111/jgs.13248
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Physician Orders for Life‐Sustaining Treatment Program in the Clinical Setting: A Systematic Review of the Literature

Abstract: The Physician Orders for Life-Sustaining Treatment (POLST) form is a palliative care tool that contains standardized, actionable medical orders. It is designed to ensure that patient treatment preferences are elicited, communicated, and honored throughout the healthcare system. A systematic review of the literature was conducted to evaluate what is currently known about the POLST program and identify directions for future research. Twenty-three research studies focused on POLST use in the clinical setting were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
156
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 35 publications
2
156
0
5
Order By: Relevance
“…Physician Orders for Life-Sustaining Treatment is a geriatric palliative care tool used in the USA that contains individualised medical orders conveying the patient’s treatment preferences when approaching end of life 11. It aims to ensure care plans on treatment decisions, and resuscitation status is documented in the patient’s medical record and honoured 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…Physician Orders for Life-Sustaining Treatment is a geriatric palliative care tool used in the USA that contains individualised medical orders conveying the patient’s treatment preferences when approaching end of life 11. It aims to ensure care plans on treatment decisions, and resuscitation status is documented in the patient’s medical record and honoured 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…Physician (or Medical) Orders for Life-Sustaining Treatment (POLST/MOLST) programs, the Institute for Healthcare Improvement conversation project, the efforts of the Coalition to Transform Advanced Care, and the "five wishes" advance directive of the Aging with Dignity organization are widely used despite the absence of compelling evidence that they improve patient outcomes. 115 Fortunately, some data are emerging. The Palliative Care in Heart Failure (PAL-HF; NCT01589601) trial is a prospective, controlled, unblinded, single center study of an interdisciplinary palliative care intervention in 200 patients with advanced heart failure estimated to have a high likelihood of mortality or readmission.…”
Section: Expanding the Evidence Basementioning
confidence: 99%
“…16 In this study, characteristics of the facilitator, including training and profession, were not assessed, although research suggests that inadequate healthcare provider training about POLST is a challenge. 9 Exploration of these factors and their relationship to discordance may help identify how best to maximize POLST decision quality. Finally, there is no information available about the rate of discordance between advance care planning documentation and current treatment preferences in a non-POLST-using sample.…”
Section: The Quality Of Polst Decisionsmentioning
confidence: 99%
“…8 Several studies have established that POLST orders are associated with the kind of treatments provided to patients near the end of life, including hospitalization and the use of cardiopulmonary resuscitation (CPR). 9 Only a few small studies have evaluated aspects of POLST decision quality. Exploratory studies have found rates of discordance between current preferences and POLST orders ranging from 9% to 29%, [10][11][12] but method issues limit the generalizability of study findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation